ASSESSMENT OF ANTIMICROBIAL AND ANTIOXIDANT ACTIVITIES OF A SPECIES OF ASPERGILLUS: AN ENDOPHYTIC FUNGUS OF SCHIMA WALLICHII (DC.) KORTH. LEAVES - Sarbadhikary, Sunrit Basu; Mandal, Narayan Chandra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The main goals of this study were to check the antimicrobial and antioxidant potentials of an endophytic fungal strain isolated from the leaves of Schima wallichii (DC.) Korth. Methods: The antibacterial and antifungal activities of the isolated fungal endophyte Visva-Bharati endophyte fungal (VBEF2) were checked by disc diffusion and agar well diffusion methods, respectively, against six pathogenic bacteria and four pathogenic fungi. The minimum inhibitory concentration (MIC) values and the mode of action of VBEF2 against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli were determined following colony-forming units (CFU) counting method. Antioxidant activity of the isolate was studied following 2, 2-diphenyl-2- picrilhydrazyl (DPPH) reduction assay. Results: The cell-free supernatants (CFS) of VBEF2 exhibited excellent antibacterial activity against all the bacteria used. The ethyl acetate extract of the endophyte was found to have the MIC of 50 Î¼g/ml and 150 Î¼g/ml against S. aureus and E. coli, respectively. It showed bactericidal mode of action against both of them. The CFS of the strain VBEF2 also showed excellent activities against two animal and two plant pathogenic fungi by producing zones of inhibition in the range of 10-20 mm. In the DPPH scavenging antioxidant assay, the ethyl acetate extract of VBEF2 was found with a low IC50 value of 19.01 Î¼g/ml. The strain VBEF2 was identified as a species of Aspergillus based on its colony morphology and structural features observed under a compound light microscope. Conclusion: The strain VBEF2 can be implemented in various fields of pharmaceutical industry as it showed multidimensional beneficial attributes such as excellent antimicrobial and antioxidant activity.